2011
DOI: 10.1111/j.1467-7687.2011.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect goal priming is more powerful than explicit instruction in children

Abstract: This study examined the relative efficacy of explicit instruction and indirect priming on young children's behavior in a task that required a series of choices between a small immediate reward and a larger delayed reward. One hundread and six 4-year-old children were randomly assigned to one of four conditions involving one of two goals (maximize rewards or obtain immediate rewards) and one of two types of instruction (indirect priming using stories or explicit verbal instructions). Children were more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
3
23
1
Order By: Relevance
“…One possibility, for the present experiments, is that once children are expert word learners they are more engaged by a learning context that they find more challenging. Similar effects have recently been found for decision making and delayed gratification in four-year-olds, i.e., that indirect goal priming is more powerful than explicit instruction for guiding children to adjust their goal settings (Kesek, Cunningham, Packer, & Zelazo, 2011). Changes in motivation are one possible route for the benefits of inferential learning that we found here.…”
Section: Discussionsupporting
confidence: 75%
“…One possibility, for the present experiments, is that once children are expert word learners they are more engaged by a learning context that they find more challenging. Similar effects have recently been found for decision making and delayed gratification in four-year-olds, i.e., that indirect goal priming is more powerful than explicit instruction for guiding children to adjust their goal settings (Kesek, Cunningham, Packer, & Zelazo, 2011). Changes in motivation are one possible route for the benefits of inferential learning that we found here.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, we found that adults’ descriptions had similar impacts on younger and older kindergarten children. These results are consistent with previous findings that, between 4 and 6 years of age, adults can influence children in various respects including what stimuli to attend to, what goal to accomplish, and what perspective to take, as well as influencing their emotion regulation, attribution, and autonomy (e.g., Kesek et al., ; Mattanah, ; Palmer & Wehmeyer, ; Qu et al., ; Qu et al., ). Together with past results, our findings emphasize the important transient feature of the kindergarten period, during which children rapidly develop the ability to regulate their behaviors but still seek information and support from their parents and teachers (e.g., Rimm‐Kaufman et al., ; Zimmer‐Gembeck & Skinner, ).…”
Section: Discussionsupporting
confidence: 92%
“…Second, an adult can help kindergarteners reflect on their own condition and, in particular, on their own essential goals and abilities. An adult can inform, explain, remind, or prime children as to what goal they should accomplish (e.g., Kesek, Cunningham, Packer, & Zelazo, ; Qu, ; Qu, Finestone, Loh, & Leong, ). Third, adults can help children analyze how the particular goal can be achieved under their particular circumstances and within their own capabilities (e.g., Palmer & Wehmeyer, ).…”
Section: Adults Can Influence Kindergarten Children's Appraisal and Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research, for example, has focused on preschool children (Blair, Zelazo, & Greenberg, 2005;Carlson, & Wang, 2007;Garcia-Molina, Enseñat-Cantallops, Tirapu-Ustárroz, & Roig-Rovira, 2009;Kesek, Cunningham, Packer, & Zelazo, 2011;Liebermann, Giesbrecht, & Müller, 2007;Müller, Dick, Gela, Overton, & Zelazo, 2006) and healthy children and teenagers between 7 and 16 years of age (Anderson, Anderson, Northam, Jacobs, & Catroppa, 2001Betts, Mackay, Maruff, & Anderson, 2006Crone, Donohue, Honomichl, Wendelken, & Bunge, 2006;Lamm, Zelazo, & Lewis, 2006;Muscara, Catroppa, & Anderson, 2008). However, these studies have been largely conducted with European and North American samples, and the number of studies conducted in Latin America is quite small by comparison (Fillipetti, 2011;Fillipetti & Minzi, 2010;Ghiglione, Fillipetti, Manucci, & Apaz, 2011;Lipina, Martelli, Vuelta, Injoque-Ricle, & Colombo, 2004).…”
Section: Introductionmentioning
confidence: 99%